2022
DOI: 10.21533/pen.v10i3.3111
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation the influence of steel-fiber on the concrete characteristics

Abstract: The impact of steel fibers on the engineering characteristics of concretes were explored experimentally in this work. Steel fibers of 0.5, 0.7, and 0.9 percent by volume fraction were applied to concretes mixture with water/cements (W/C) proportions of 0.43 to accomplish this. There has been a total of 24 cubic specimens produced for compressive strengths testing, 24 cylindrical specimens for splitting tension strengths testing, and 12 cubic specimens for toughened unit weight testing. The experimental finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…It was determined that the workability of concrete reinforced with fibres decreases with an increase in fibre volume, especially after the rate of 0.75 % steel fibre, and the degree of slump entered the S3 consistency class at the rate of 1.50 % steel fibre. The results of the current study are compatible with those in the literature [31], as it has been observed in the literature that the workability of concrete mixtures decreases after a 0.8 % steel fibre ratio in studies using different ratios of steel fibres [32,33].…”
Section: Slump Test Resultssupporting
confidence: 93%
“…It was determined that the workability of concrete reinforced with fibres decreases with an increase in fibre volume, especially after the rate of 0.75 % steel fibre, and the degree of slump entered the S3 consistency class at the rate of 1.50 % steel fibre. The results of the current study are compatible with those in the literature [31], as it has been observed in the literature that the workability of concrete mixtures decreases after a 0.8 % steel fibre ratio in studies using different ratios of steel fibres [32,33].…”
Section: Slump Test Resultssupporting
confidence: 93%
“…There is a current demand for strengthening numerous reinforced concrete (RC) structures, particularly in developing nations (Al-Khafaji et al, 2021;Ali et al, 2022;Falah et al, 2020). The process of demolishing old buildings and constructing new ones is both financially burdensome and time intensive.…”
Section: Introductionmentioning
confidence: 99%